PENINGKATAN KESEJAHTERAAN PETANI DENGAN KONSEP GREEN ECONOMY LIMBAH BUAH JERUK NIPIS (Citrus aurantifolia) SEBAGAI BAHAN POMADE ANTI KETOMBE - Oryza Sativa, Rima Dewi; Wahyu Budiman, Eko; Febrianti, Neha (Universitas Islam Balitar, 2024)
Pomade is a styling material that is usually used by men with strong adhesion and a shiny finish. The potential of the lime part, especially lime waste as a natural hair care combined with mixed ingredients such as olive oil, castor oil, can be produced in the form of pomade hair oil. The purpose of this study is to find out the use of lime waste to improve the economy of farmers, to know the advantages and marketing strategies of lime waste treatment products. This activity is in collaboration with lime farmers of the